Microstructure and mechanical properties of a low-alloyed Mg–Zn–Al–Ca alloy: Effect of extrusion speed - L. Liu; H. Wang; D.T. Zhang; C. Qiu; D.L. Chen (Journal of Materials Research and Technology)
A low-alloyed Mg-1.2Zn-0.6Al-0.1Ca (wt.%) alloy was extruded at 200 °C with different ram speeds (0.5–4.0 mm/s), and the microstructure and mechanical properties were studied systematically. Heterostructures with fine dynamic recrystallized (DRXed) grains and coarse unDRXed grains were achieved at lower ram speeds of 0.5 mm/s and 1.0 mm/s, and fully-DRXed microstructure was attained at 4.0 mm/s. Increasing the extrusion speed resulted in an increase in DRXed grain size from 0.9 μm to 3.8 μm, and a transformation of the DRXed texture component from <10 to 10>−<11–20> to a new orientation that deviated by approximately 14°. The sample extruded at 0.5 mm/s presented an excellent tensile yield strength (TYS) of 369 MPa along with a 7.8% elongation, which was mainly due to the high hetero-deformation induced (HDI) strengthening provided by its heterostructures. Increasing ram speed resulted in an improved elongation despite a decreased TYS. The reasons for the decreased strength with increasing extrusion speed were mainly associated with grain growth, reduced dislocation density and weakened HDI strengthening. The reasons for the improved ductility with increasing extrusion speed were largely due to the increased DRXed grains fraction with soft orientations.